"Covalent biosensing" enables a one-step, reagent-less, low-cost and highly robust assay of SARS-CoV-2. Issue 82 (29th September 2021) - Zhang, Kai; Li, Jinlong; Fan, Zhenqiang; Li, Hao; Xu, Jing-Juan
Abstract : A one-step, reagent-free, low-cost, high-stability assay for the detection of SARS-CoV-2. Abstract : We have established a new protocol for detecting severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) using a peptidomimetic to covalently detect a viral marker protease.